Validation of visual analog scales of mood and anxiety at the workplace. - Frédéric Dutheil; Clara Palgen; Georges Brousse; Thomas Cornet; Martial Mermillod; Ines Lakbar; Guillaume Vallet; Julien S Baker; Jeannot Schmidt; Barbara Charbotel; Bruno Pereira; Louis Delamarre (PLoS ONE)
The Hospital Anxiety and Depression Scale (HADS) is commonly used to detect depressive or anxious states, but its 14-item questionnaire is time-consuming. Visual analog scales (VAS) are easy to use and quick to implement. Although the VAS has been validated to assess pain and occupational stress, VAS scores for anxiety and mood have never been evaluated in the workplace. We aimed to validate the use of visual analog scales (VAS) for anxiety and mood compared to HADS in workers. A HADS self-reported questionnaire associated with VAS assessing perceived anxiety and mood on a horizontal line of 100 mm was administered to 182 workers, with a second test (retest) proposed one week later. Sociodemographic, characteristics of work, sleep, well-being, and stress were also assessed. VAS anxiety and mood correlated with the HADS sub-scores (0.70 and 0.65, respectively). The test-retest reliability was good. Optimal VAS cut-offs were ≥ 60/100 for anxiety and ≤ 60/100 for mood, to define at-risk patients. The VAS is quick to perform, easy to use, and reliable for screening depression and anxiety in occupational medicine. We recommend validated questionnaires for at-risk patients. Trial registration Clinicaltrials gov: NCT02596737. Available at: https://www. Clinicaltrials gov/ct2/show/NCT02596737.